2 years of seismic parameters calculated at FLUR station prior, during, and after the 2014-2015 Holuhraun eruption, Iceland ... - Sudibyo, Maria R.P.; Eibl, Eva P.S.; Hainzl, Sebastian; Ohrnberger, Matthias (GFZ Data Services, 2024)
A seismic station installed in the vicinity of a volcano can provide an overview of the state of the volcano. Different observable parameters can be extracted from the seismic time series to help monitor the temporal changes that preceding and accompanying a volcanic eruption. We calculated five seismic parameters which are Permutation Entropy (PE), Phase Permutation Entropy (PPE), Instantaneous Frequency (IF), Root-Mean-Square and Root-Median-Square (RMeS) of the seismic amplitude to detect changes prior and during the 2014-2015 Holuhraun eruption in Iceland. ...